Research Methods – Data Analysis Techniques - Tominc, Polona; Čančer, Vesna; Rožman, Maja (University of Maribor Press, 2026)
The tutorial Research Methods – Data Analysis Techniques is intended for master’s students of the programme Economic and Business Sciences, specialization Data Science in Business. It provides a systematic and practice-oriented overview of quantitative methods and statistical analyses using the SPSS software. The material connects theoretical foundations with real-world business examples, encouraging the development of data literacy and analytical reasoning. It covers topics such as descriptive statistics, sampling, normal distribution, parametric and nonparametric tests, regression and factor analysis, time series analysis, discriminant analysis, and Monte Carlo simulation. The publication equips students with practical research and analytical skills essential for understanding contemporary data-driven challenges and for making evidence-based decisions in business environments.